Analysis of Students’ Concept Mastery Profile on Direct Current Electricity Topic (Case Study of SMAN 2 Kabupaten Tangerang) - Fathiah Damri Said (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2022)
Seldom do the the assessment results used as information in didactic analysis to improve the learning process. This study aims to develop ways of delivering the concept of direct current electricity based on the results of the analysis of students' mastery of physics concepts. Descriptive research was conducted on students in a public high schools in Tangerang. The results denoted that the concept mastery of electrical resistivity of materials and electrical safety systems were categorized as low. Didactic analysiswas built contextually by integrating the physical phenomena of direct current electricity in technology and everyday life. This pilot study will provide information for further researches in an way to develop a didactic design in presenting the concept of direct current electricity.